Uma abordagem sensorial e quimica ao aroma de aguardentes vinicas envelhecidas da Lourinhã - Sousa, Raul Bruno de (2009)
The maturation of wine brandies in wooden barrels origin many sensory and physical-chemical changes in these alcoholic beverages. This work studies the odorants in different aged brandies from Lourinhã. These brandies were analyzed by gas chromatography coupled to olfactometry (CG-O). A panel taster profiled these brandies and the identified odorants were also quantified by gas chromatography coupled to a flame ionization detector (CG-FID). The CG-O results showed 29 identified odorants (alcohols, esters, acids and phenols. Some of them are proceeding from the distillate while others are extracted from the wood. The analysis of the correlation between the sensory profiles and the odorant quantification pointed out the relevance of several wood compounds for the brandy aroma, namely the vanillin, volatile phenols and furanic aldehydes. These compounds presented important correlations with several olfactory attributes like vanilla, toasted dried fruits, woody, which influence positively the quality of the brandies.